Matching for Credit: Identifying information asymmetries in joint-liability lending - Thilo Klein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Microcredit, a financial tool providing uncollateralized loans to low-income individuals, has seen a shift from joint-liability (JL) to individual liabil- ity (IL) lending models. This article tests a theory explaining this shift, focusing on borrowers matching into groups exposed to similar economic shocks under JL, diminishing its effectiveness. I reconcile conflicting theo- retical predictions and propose an empirical strategy to distinguish adverse selection from moral hazard effects. Using data from Thailand, I find that increasing diversity within borrower groups leads to a 10 percentage point improvement in timely repayment. These results inform contract design and strategies to reduce information asymmetries in lending practices
Keywords: C11; C31; C34; C36; C78; C57; D02; D47; D82; G21; O16; Q14; 330; microcredit; joint liability; diversification; market design; stable matching; endogeneity; selection model; agriculture; Thailand